2012
DOI: 10.1387/ijdb.113483hm
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pattern formation in hydra: a route to understanding essential steps in development

Abstract: Modeling of pattern formation in hydra has revealed basic mechanisms that underlie the reproducible generation of complex and self-regulating patterns. Organizing regions can be generated by a local self-enhancing reaction that is coupled with an inhibitory effect of longer range. Such reactions enable pattern formation even in an initially almost homogeneous assembly of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 66 publications
(107 reference statements)
3
110
0
Order By: Relevance
“…Numerical computations have confirmed this behaviour [19]. This is in agreement with the pattern of multiple spikes covering the whole interval computed in our paper (see Figures 4-6).…”
Section: Resultssupporting
confidence: 91%
“…Numerical computations have confirmed this behaviour [19]. This is in agreement with the pattern of multiple spikes covering the whole interval computed in our paper (see Figures 4-6).…”
Section: Resultssupporting
confidence: 91%
“…In this form, the Wnt molecules are much more mobile. Although it has not yet been shown that the differently processed Wnt molecules have different functions, from our model we would expect that the slowly diffusing variety is involved in the selfenhancement while the long-ranging variety undermines this self-enhancement [27]. The following set of equations describes a highly simplified version of this reaction scheme.…”
Section: The Wnt Pathway: the Conversion Of An Activator Into An Inhimentioning
confidence: 99%
“…Many of the bioinformatic approaches applied to precision medicine are currently concerned with diagnosis and treatment response prediction by molecular stratification of patients using genetic and more generally omic profiling. However, computational mathematical models are being generated to predict mode-of-action and responses-to-treatments (perturbations) not just at the molecular level but across all levels of biological organisation, including molecular, gene regulatory networks, signal transduction pathways and metabolic networks, cell populations, tissue level and whole organism models [10,[35][36][37][38]. In addition, models are being generated to account for pharmacokinetics and pharmacodynamics to analyse drug action, and even human-population level pharmacogenomics models of disease risk [10,39,40].…”
Section: Precision Medicine Approachesmentioning
confidence: 99%